Remimazolam-based precision anesthesia management combined with nasopharyngeal airway in gastroscopic surgery for a patient with obesity and difficult airway: a successful case report - Ji, Hui; Xie, Mengran; Wang, Hao; Pei, Huanshuang (Frontiers in Medicine, 2026)
BackgroundPatients with moderate obesity, obstructive sleep apnea hypopnea syndrome (OSAHS), and an anticipated difficult airway are at high risk for hypoxemia and airway complications under deep sedation.CaseThe initial procedural attempt was aborted due to propofol-induced respiratory complications, including pronounced coughing and severe hypoxemia, in a high-risk patient with obesity and a Mallampati Class III airway. The subsequent optimized anesthetic protocol involved proactively establishing a patent upper airway with a lubricated nasopharyngeal conduit. Sedation was then carefully induced using remimazolam, a novel ultra-short-acting benzodiazepine chosen for its superior cardiorespiratory stability. This strategy successfully maintained spontaneous ventilation and stable hemodynamics throughout the entire gastroscopy procedure, enabling immediate reversal with flumazenil and facilitating rapid postoperative recovery.ConclusionThis case demonstrates that for high-risk patients, the “precise sedation with preserved spontaneous breathing” strategy using remimazolam combined with a nasopharyngeal airway is a safe, effective, and reversible innovative anesthesia option.